(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Culture filtrates collected from Trichoderma harzianum were assayed to control seed-borne fungi of selected vegetables viz. bottle gourd, wax gourd, sweet gourd, snake gourd and okra. Three fungal genera comprising of four species viz. Aspergillus niger, Aspergillus flavus, Penicillium spp. and Fusarium oxysporum were found to be associated with most of the vegetable seeds. Among the seed borne fungi the highest incidence was recorded in case of A. niger (49.2%) followed by A. flavus (40.6%) and F. oxysporum (40.2%). Five treatments viz. 1%, 3%, 5%, 7% aqueous solution of culture filtrates and control (without culture filtrate) were assayed against individual seed-borne fungal pathogen following poison food technique. Among the treatments, 7% aqueous solution of culture filtrate showed superior performance by suppressing mycelial growth of all fungal genera and this treatment was further considered to treat the seeds to control seed borne fungi. Prevalence of seed-borne A. niger, A. flavus, Penicillium spp. and F. oxysporum were reduced significantly by seed treatment with 7% aqueous solution of culture filtrates. The findings of the study suggested that seed priming by aqueous solution of culture filtrates of Trichoderma (7%) can be used for vegetable seed treatment for controlling seed- borne fungal infection. J Bangladesh Agril Univ 18(1): 12–16, 2020 https://doi.org/10.5455/JBAU.94724